IMPROVED OBJECT SEGMENTATION USING MULTI SCALE SALIENCY APPROACH - Thilagamani, S; Manochitra, V (International Journal of Computer Sciences and Engineering, 2025)
Visual saliency endeavors to decide the measure of consideration guided towards different locales in a picture in the human pictorial and intellectual systems. It is thusly a focal issue in knowledge explore, neural science, and PC vision. PC vision examiners spin around influencing computational models for either recreating the human visual idea to process or suspecting visual saliency happens as expected. Visual saliency has been consolidated in a gathering of PC vision and picture getting ready endeavors to improve their execution.In this paper aims to correctly popping up the complete salient object(s). Salient object detection aims to correctly highlight the most salient object(s) in an image. Then we formulate saliency map computation as an regression problem,utilizes the supervised learning approach to map the regional feature vectors to detect the saliency scores. The regional feature vector includes contrast and background details. Random forest regressors with multilevel segmentation algorithms can be used to detect the salient object regions with improved accuracy rate. Experimental results provide improved clustered accuracy for real time datasets and are fit for accomplishing cutting edge execution on all open benchmark datasets.